Agent-based modeling for the self-management of chronic diseases: An exploratory study. (September 2017) - Montagna, Sara; Omicini, Andrea
The impact of mobile technologies on healthcare is particularly evident in the case of self-management of chronic diseases, where they can decrease spending and improve life quality of patients. We propose the adoption of agent-based modeling and simulation techniques as built-in tools to dynamically monitor the state of patient health and provide recommendations for self-management. To demonstrate the feasibility of our proposal we focus on Type 1 diabetes mellitus as our case study, and provide simulation results where the dynamic evolution of signal parameters is shown in the case of healthy and Type 1 diabetes mellitus patients, focussing in particular on the beneficial effects that self-management interventions have on plasma glucose values.